2007
DOI: 10.1080/09540120701203386
|View full text |Cite
|
Sign up to set email alerts
|

Sex work and risk behaviour among HIV-negative gay men

Abstract: Gay men who engage in sex work may be at increased risk through risk behaviour outside the context of sex work. Among participants in the Health in Men (HIM) cohort of HIV-seronegative gay men in Sydney, 19.7% had ever engaged in sex work. Five percent reported being paid for sex in a six-month period during the study (2001-2006); a minority (18.3%) of these current sex workers reported unprotected anal intercourse (UAI) with clients and 62.0% reported UAI with any casual partners. The practice of sex work its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 28 publications
3
25
2
Order By: Relevance
“…After adjusting for other factors, no differences were observed in the prevalence of HIV, chlamydia or gonorrhoea between MSS and other MSM. Although no difference in the frequency of condom use was observed between MSS and other MSM in this study, previous investigation has found condom use to be higher among MSM when engaged in sex work than in other sexual encounters [46,47]. A potentially increased risk of rectal STIs among MSS due to a higher frequency of anal receptive intercourse may have been mitigated by an increased frequency of condom use while engaged in sexselling, although overall condom-use frequency did not vary between groups and many study participants reported condomless sex.…”
Section: Discussioncontrasting
confidence: 90%
“…After adjusting for other factors, no differences were observed in the prevalence of HIV, chlamydia or gonorrhoea between MSS and other MSM. Although no difference in the frequency of condom use was observed between MSS and other MSM in this study, previous investigation has found condom use to be higher among MSM when engaged in sex work than in other sexual encounters [46,47]. A potentially increased risk of rectal STIs among MSS due to a higher frequency of anal receptive intercourse may have been mitigated by an increased frequency of condom use while engaged in sexselling, although overall condom-use frequency did not vary between groups and many study participants reported condomless sex.…”
Section: Discussioncontrasting
confidence: 90%
“…This study demonstrates the achievement of our community mobile unit to draw out the hard-to-reach populations, who otherwise may have not been tested 28. As the study was performed in public venues rather than a medical setting, its findings can be used as a rough estimation of the prevalence of STI/HIV among MSM in Tel Aviv.…”
Section: Discussionmentioning
confidence: 82%
“…For the pH study, comparison data were based on the 293 HIV‐positive men who completed both the main and the optional sexual behavioral questionnaires at the 2006–2007 data collection round. For the HIM study, the comparison was based on the 1,427 HIV‐negative men who completed the baseline survey between 2001 and 2004 [18]. It should be noted that in the two community studies (the pH and HIM cohorts), many of the same sexual problem questions were asked, but the recall period was 6 months prior to survey.…”
Section: Methodsmentioning
confidence: 99%